Small-bowel necrosis associated with jejunal tube feeding - Lawlor, D. Kirk (Canadian Medical Association, 1998)
OBJECTIVES: To report 3 cases of small-bowel necrosis after jejunal tube feeding and to review the literature concerning this condition. DESIGN: A 5-year retrospective review. SETTING: A 560-bed university-affiliated tertiary-care teaching hospital. PATIENTS: Three patients who had bowel necrosis out of 386 who received jejunal tube feedings. RESULTS: The patients experienced small-bowel necrosis as a consequence of jejunal feeding. The ischemic necrosis was preceded by progressive abdominal pain, distension and high nasogastric output. All 3 patients required extensive small-bowel resection. Although survival was rare in previous reports, our 3 patients survived after prompt surgical intervention and small-bowel resection. CONCLUSIONS: Although the death rate for this condition approaches 70%, timely recognition and surgical intervention can save the patient’s life.